A Patient Diagnosed with POEMS Syndrome with Atypical Presentation - Seyin Semiz H; Sarıkaya O; Duran M; Ozsan N; Saydam G (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2018)
POEMS syndrome is a paraneoplastic syndrome due to an underlying plasma cell neoplasm. The major criteria for the syndrome are polyradiculoneuropathy, clonal plasma cell disorder (PCD), sclerotic bone lesions, elevated vascular endothelial growth factor, and the presence of Castleman disease. Minor features include organomegaly, endocrinopathy, characteristic skin changes, papilledema, extravascular volume overload, and thrombocytosis [1]. Autologous Stem Cell Transplantation (ASCT) might be potential approach of choice in patients that are eligible; otherwise, systemic therapies adopted from the therapeutic armamentarium for multiple myeloma are alternatives [2]. İn this paper, we reported that a patient which was treated with VAD (Vincristine, Doxorubicin, Dexamethasone 40 mg) with exlusion of vincristine due to existing neuropathy and ASCT with high-dose melphalan and improved; although the bone marrow biopsy did not observe a plasma cell clone.